ADAPTABILITY AND STABILITY OF IRRIGATED RICE ELITE LINES FOR GRAIN QUALITY - Facchinello, Paulo Henrique Karling; Streck, Eduardo Anibele; Aguiar, Gabriel Almeida; Oliveira, Victoria Freitas de; Goveia, JanaÃna; Feijó, Michele; Vasconcellos, Matheus Leite; Carvalho, Ivan Ricardo; Fagundes, Paulo Ricardo Reis; Maia, Luciano Carlos da; et al. (REVISTA DE AGRICULTURA, 2022)
The objective of this work was to investigate the interaction of irrigated rice genotypes in different environments, based on the genotypic evaluation of grain quality traits, through the adaptability and stability analysed by mixed models. These parameters were obtained from cultivation trials in eight cultivation environments of irrigated rice in Southern Brazil. The experimental design was randomized complete blocks, with 14 genotypes for each one and four repetitions. The genotypic values were estimated using REML/BLUP, based on the harmonic mean methods of the genotypic values, the relative performance of the predicted genotypic values through the environments and the harmonic mean of the relative performance of the genotypic values. The high accuracy values obtained for the most studied variables, show a great experimental quality and safety in the selection of these traits. The lines AB11502 and AB10501 showed a better agronomic performance in the milling yield. AB13008, AB13002 and AB13003 stood out for plaster traits, showing higher adaptability and stability. These inbred lines revealed high potential for grain quality attributes, and have potential to be released.